Spirit baptism : the Pentecostal experience in theological focus - Perry, David, 1981- (Global Pentecostal and Charismatic Studies, 2017)
The Pentecostal experience of Spirit baptism remains an important topic of discussion more than a century after the inception of the Pentecostal movement. In Spirit Baptism: The Pentecostal Experience in Theological Focus David Perry moves beyond traditional debates by focusing on the meaning and function of the experience within the Pentecostal community. Grounded in the Pentecostal experience itself, he explores the meaning of the experience in terms of its cognitive, effective, constitutive and communicative function. He demonstrates the enduring value of the experience of Spirit baptism to the Pentecostal community and emphasises what is centrally important - a powerful and transformative encounter with the Holy Spirit.